Efektivitas Biofungisida Jamur Trichoderma harzianum dan Trichoderma koningii dengan Berbagai Dosis terhadap Intensitas Serangan Penyakit Layu Jamur Fusarium pada Tanaman Cabai Merah (Capsicum annum L.) - Sadin, Yuliana Ivantri; Julyasih, Ketut Srie Marhaeni; Manalu, Jean Nihana (UNIVERSITAS LABUHANBATU, 2025)
Red chili is a horticultural crop that is already widely cultivated in Indonesia. The main constraint faced by farmers is the attack of plant pests, namely Fusarium wilt disease. One alternative control method is the use of biofungicides containing the fungi T. harzianum and T. koningii. This research was conducted in two different locations: isolation of the pathogenic fungus Fusarium, identification of Trichoderma fungi, and mass production of T. harzianum and T. koningii using rice medium at the Biological Agents / Botanical Pesticides Laboratory, Biaung. The planting of red chili seedlings and the application of biofungicides were carried out in the field of the Biological Agents / Botanical Pesticides Laboratory on Jalan Tegal Harum, Gang Sakura, Biaung, East Denpasar District, Denpasar City, Bali, from May to August 2025. The experimental design used was a Completely Randomized Design (CRD) with 7 treatments and 5 replications. The treatments were: 0 grams of biofungicide of T. harzianum and T. koningii fungi, a dose of 10 grams, a dose of 20 grams, a dose of 30 grams of T. harzianum biofungicide, and doses of 10 grams, 20 grams, and 30 grams of T. koningii biofungicide. Statistically, the application of different doses of T. harzianum and T. koningii biofungicides produced a significant difference in suppressing the intensity of Fusarium wilt disease, as shown by the one-way ANOVA test (p<0.05). The use of T. harzianum and T. koningii biofungicides at a dose of 30 grams proved effective against Fusarium wilt, with the level of suppression reaching 100% after four weeks of application. Keywords: Fusarium Wilt, red chili pepper, Trichoderma harzianum, Trichoderma koningii.